ASAS PRESUMPTION OF INNOCENCE DALAM PERLINDUNGAN HAK ASASI MANUSIA SEBAGAI LANDASAN KEADILAN - Aji rahman Halim (Universitas Majalengka, 2022)
Abstract The existence of the principle of presumption of innocence is important both from the point of material criminal law and criminal procedural law, especially from the point of view of human rights. However, in the practice of criminal justice, there are still deviations and abuses of authority, both because of the weaknesses of the normative provisions as well as differences in perceptions among law enforcers (especially prosecutors and judges). The research method used in this study is descriptive analysis and the approach used in this research is a normative juridical approach, namely by reviewing or analyzing secondary data in the form of secondary legal materials by understanding the law as a set of regulations or positive norms in the system. legislation that regulates the problems in this research. After the secondary and primary data were collected, a qualitative analysis was then carried out. Based on the results of data analysis, it is concluded that the recognition of the principle of the presumption of innocence is closely related to human rights that must be respected and upheld, and the rights of the suspect or defendant must also be respected. To support the principle of presumption of innocence in law enforcement, the Criminal Procedure Code has provided a set of rights that must be respected and protected by law enforcers. Keberadaan asas praduga tidak bersalah sangat penting baik dari sudut hukum pidana materil maupun hukum acara pidana, terutama dari sudut pandang hak asasi manusia. Namun, dalam praktik peradilan pidana, masih terdapat adanya penyimpangan dan penyelewengan wewenang baik karena adanya kelemahan-kelemahan dari ketentuan normatif maupun serta perbedaan persepsi di kalangan penegak hukum (khususnya jaksa dan hakim) Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif analisis dan pendekatan yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif, yaitu dengan mengkaji atau menganalisis data sekunder yang berupa bahan-bahan hukum sekunder dengan memahami hukum sebagai perangkat peraturan atau norma-norma positif di dalam sistem perundang-undangan yang mengatur mengenai permasalahan dalam penelitian ini. Setelah data sekunder dan primer terkumpul, kemudian diadakan analisis secara kualitatif . Berdasarkan hasil analisis data, disimpulkan bahwa Pengakuan tentang asas praduga tak bersalah berhubungan erat dengan hak-hak asasi manusia yang harus dihormati dan dijunjung tinggi. serta hak-hak tersangka atau terdakwa juga harus dihormati. Untuk menopang asas praduga tak bersalah dalam penegakan hukum, maka KUHAP telah memberikan seperangkat hak yang wajib dihormati dan dilindungi oleh para penegak hukum.